2022
DOI: 10.1146/annurev-bioeng-110320-110749
|View full text |Cite
|
Sign up to set email alerts
|

Cell Trafficking at the Intersection of the Tumor–Immune Compartments

Abstract: Migration is an essential cellular process that regulates human organ development and homeostasis as well as disease initiation and progression. In cancer, immune and tumor cell migration is strongly associated with immune cell infiltration, immune escape, and tumor cell metastasis, which ultimately account for more than 90% of cancer deaths. The biophysics and molecular regulation of the migration of cancer and immune cells have been extensively studied separately. However, accumulating evidence indicates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 206 publications
0
18
0
Order By: Relevance
“…Our findings that suppression of tumor progression and metastasis by iEF treatment was contingent on an intact immune system led us to analyze the effect of iEFs on the tumor immune microenvironment. The migratory behavior of macrophages can influence tumor progression 32,33 and plays a crucial role in coordinating immune responses and inflammation 34,35 . Thus, we first assessed the direct effect of iEF treatment on immune cell migration.…”
Section: Ief Treatment Reduces Immunosuppressive Features Of Tnbcmentioning
confidence: 99%
“…Our findings that suppression of tumor progression and metastasis by iEF treatment was contingent on an intact immune system led us to analyze the effect of iEFs on the tumor immune microenvironment. The migratory behavior of macrophages can influence tumor progression 32,33 and plays a crucial role in coordinating immune responses and inflammation 34,35 . Thus, we first assessed the direct effect of iEF treatment on immune cell migration.…”
Section: Ief Treatment Reduces Immunosuppressive Features Of Tnbcmentioning
confidence: 99%
“…1a, 1). Next, these cells migrate through the tissue’s stromal matrix toward tumor cells via chemokine/cytokine directed chemotaxis and/or random migration [5] (Fig. 1a, 2).…”
Section: Introductionmentioning
confidence: 99%
“…These assays focus exclusively on proximity-mediated cell recognition and killing by co-seeding immune cells with cancer cells or overlaying immune cells onto a monolayer of cancer cells on a culture plate [9][10][11]. Yet, the ability of immune cells to travel to the tumor site is an essential cellular attribute when evaluating their overall cytotoxic effect in solid tumors [4,5,[12][13][14]. The physical barriers dividing the collagen-rich stromal region from the tumor where cancer cells deposit the components of a basement membrane (i.e., laminins and collagens) cannot be replicated in 2D systems [6][7][8]15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have confirmed that immunomodulation plays an important role in cancer progression, and thus, immunotherapy has been a major driving force for individualized cancer medicine [ 5 ]. Immune cell infiltration in the tumor microenvironment plays an important role in tumor progression [ 6 ]. However, the mechanisms of immune cell infiltration into the tumor microenvironment of ccRCC are still not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%